Investigation of the Attenuation Rate of a Ultrawideband Wave Outdoors in a Two-Ray Model - Andreyev, Yu. V.; Petrosyan, M. M. (Journal of communications technology & electronics, 2023)
The features of propagation of an ultrawideband (UWB) wave over Earth’s surface in a two-ray model are studied. It is shown that there is a limiting distance (break point) up to which the UWB wave attenuates approximately as in free space with pathloss exponent n = 2 without experiencing fading due to the extremely short UWB autocorrelation time; beyond the break point, the wave attenuation exponent becomes equal to n = 4.